Agents for Educational Games and Simulations International Workshop, AEGS 2011, Taipei, Taiwan, May 2, 2011. Revised Papers - Beer, Martin; Brom, Cyril; Dignum, Frank; Soo, Von-Wun.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book consists mainly of revised papers that were presented at the Agents for Educational Games and Simulation (AEGS) workshop held on May 2, 2011, as part of the Autonomous Agents and MultiAgent Systems (AAMAS) conference in Taipei, Taiwan. The 12 full papers presented were carefully reviewed and selected from various submissions. The papers are organized topical sections on middleware applications, dialogues and learning, adaption and convergence, and agent applications.
Middleware applications -- dialogues and learning -- adaption and convergence -- agent applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Computer Communication Networks; Software Engineering; Simulation and Modeling